SPECIALIZED SUPPLEMENTS IN THE FIRST THIRD OF THE 20TH CENTURY: A CASE STUDY - Serra, Carolina; Martorell, Cristina (Revista de Historia Social y de las Mentalidades, 2025)
The modernization of newspaper companies during the first third of the 20th century pushed them to launch new initiatives, such as the creation of specialized supplements, in order to improve their income, broaden their readership and offer advertisers more segmented advertising space. This paper analyzes the five specialized supplements published by the newspaper Las Noticias with the aim of providing unpublished data on the appearance and evolution of these publications. For the analysis of the primary sources, more than 500 copies of the newspaper and a hundred supplements were consulted in the Historical Archive of the City of Barcelona, as well as secondary sources. The analysis of these supplements confirms their usefulness to reach new audiences and to maintain or increase subscriptions to the newspaper.